2022
DOI: 10.5334/gh.1088
|View full text |Cite
|
Sign up to set email alerts
|

Hypertension and Socioeconomic Status in South Central Uganda: A Population-Based Cohort Study

Abstract: Background: Limited studies exploring the impact of socioeconomic status (SES) on hypertension in Africa suggest a positive association between higher SES and hypertension. The economic development in sub-Saharan African countries has led to changes in SES and associated changes in lifestyle, diet, and physical activity, which may affect the relationship between hypertension and SES differently compared with higher income countries. This cross-sectional study from a large populationbased cohort, the Rakai Comm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 17 publications
3
13
0
Order By: Relevance
“…In this study, the probability of being overweight or obese increased with SES, similar to past research in Uganda [13,36,37], sub-Saharan Africa [3,24,25,38] and low-and middleincome countries [39]. This trend differs from that of high-income countries where the prevalence of overweight and obesity decreases with wealth [40].…”
Section: Plos Global Public Healthsupporting
confidence: 87%
“…In this study, the probability of being overweight or obese increased with SES, similar to past research in Uganda [13,36,37], sub-Saharan Africa [3,24,25,38] and low-and middleincome countries [39]. This trend differs from that of high-income countries where the prevalence of overweight and obesity decreases with wealth [40].…”
Section: Plos Global Public Healthsupporting
confidence: 87%
“…A study in the Korean population also found a similar directional association 53 . More studies focused on the independent association between ES and hypertension and diabetes separately, especially in developing countries, and reported a positive association 34,54–57 . Obesity rates have risen with urbanization and gross domestic product growth, accompanied by shifts in diet and reduced activity.…”
Section: Discussionmentioning
confidence: 79%
“…The prevalence of raised fasting glucose including diabetes was 3.3%, and close to 90% of participants who were found to have a raised fasting glucose were not on medication nor aware of their hyperglycaemia [9]. The prevalence of hypertension among adults in our study population is estimated at 20.8% [10].…”
Section: Introductionmentioning
confidence: 84%